If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5 + -9x) * x + -1x(3x + 5) = (2 + -12x) * x Reorder the terms for easier multiplication: x(5 + -9x) + -1x(3x + 5) = (2 + -12x) * x (5 * x + -9x * x) + -1x(3x + 5) = (2 + -12x) * x (5x + -9x2) + -1x(3x + 5) = (2 + -12x) * x Reorder the terms: 5x + -9x2 + -1x(5 + 3x) = (2 + -12x) * x 5x + -9x2 + (5 * -1x + 3x * -1x) = (2 + -12x) * x 5x + -9x2 + (-5x + -3x2) = (2 + -12x) * x Reorder the terms: 5x + -5x + -9x2 + -3x2 = (2 + -12x) * x Combine like terms: 5x + -5x = 0 0 + -9x2 + -3x2 = (2 + -12x) * x -9x2 + -3x2 = (2 + -12x) * x Combine like terms: -9x2 + -3x2 = -12x2 -12x2 = (2 + -12x) * x Reorder the terms for easier multiplication: -12x2 = x(2 + -12x) -12x2 = (2 * x + -12x * x) -12x2 = (2x + -12x2) Add '12x2' to each side of the equation. -12x2 + 12x2 = 2x + -12x2 + 12x2 Combine like terms: -12x2 + 12x2 = 0 0 = 2x + -12x2 + 12x2 Combine like terms: -12x2 + 12x2 = 0 0 = 2x + 0 0 = 2x Solving 0 = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 0 + -2x = 2x + -2x Remove the zero: -2x = 2x + -2x Combine like terms: 2x + -2x = 0 -2x = 0 Divide each side by '-2'. x = 0 Simplifying x = 0
| 3+2(x-4)=1 | | 0.0364b=10.4 | | 25-0.4x=0 | | -5(-2x+4)-6(4x+5)=36 | | 1/8^0.5-1=4 | | 16-8=24 | | y=x^2+9x+c | | 8x^2+12x-7=0 | | 2377960-300000026= | | 11+7(3x-3)=2[3(5x+3)+4] | | 5-9(4x+2)=3 | | 0=16t^2+112t-4296 | | 5-2(2-x)=-2 | | 8x^2+18x+4/4x+3 | | -8-18= | | 0.6a=12 | | 1/5(-3x+5)-3(4x+5)=2/5 | | -5*3.6+1= | | 4-2(y+1)=-2 | | 66p*p+57p+12=0 | | 9a+12-a=28 | | 3x+2y=115 | | 3x+8=3-2x | | 2=3+7y-4y-6-5y | | 2(x+1)=x+8 | | 3(m-5)=24 | | 2=3+7y-4y-6y-6y-5y | | -5x+4=-6x+16 | | 2=3+7y-4y-6y-6-5y | | 200x-x^2=2100 | | 10x+20(x-2)=470 | | 7-(3x-4)+5x=35 |